Traffic Capacity Assessment of the Urban Elevated Bridge after Near-Field Explosion Based on the Response Surface Method - Jinghui Jiang (Shock and Vibration, 2020)
The traffic capacity of the urban elevated bridge is assessed after it is attacked by a near-field explosion, using the residual bearing capacity of the damaged pier as the assessment index. First, the finite element model of a reinforced concrete slab under near-field explosion is established by ANSYS/LS-DYNA software and compared with the experimental results, which verifies the effectiveness of the ALE (arbitrary Lagrangian–Eulerian) algorithm and the accuracy of the mesh size and material properties. Then, an “explosive-air-pier” coupling analysis model is constructed using the finite element method, and the damage of the reinforced concrete pier under three types of car bombs is evaluated. Furthermore, a response surface model for the residual bearing capacity of the pier is utilized to calculate the failure probabilities of various damage levels of the pier under the three types of car bombs and to assess the traffic capacity of the bridge after near-field explosion. The established assessment method can be used to predict the probability of bridge structural damage at various levels under different types of car bombs and to provide a reference for exploring a probability-based safety assessment method of post-explosion bridges.